The impact of labour force reduction on financial performance of manufacturing companies: A case study of Playtime Manufacturers (2011 – 2016) - Gwangwadza, Denzel Chengetai (Midlands State University, 2020)
This research was conducted with the aim of determining the impact of employing labour force reduction initiatives on financial performance of manufacturing companies. The research focused on Playtime Manufacturers a garment manufacturing company that has been reducing its labour force since 2012. The researcher adopted mixed methodology incorporating both qualitative and quantitative methodology. A descriptive and correlation research design was used to gather data. Primary data was collected from the total target population through interviews and questionnaires. A census was used to ensure that there was no bias and that findings could be generalised to the entire organisation with accuracy. In addition to primary data analysis the researcher analysed secondary data to triangulate research instruments and validate findings. The first major findings was that manufacturing companies in Zimbabwe used layoffs, furloughs outsourcing and delayering as labour force reduction methods. The second finding was the importance of communication and employee involvement in preventing production efficiency drops and production costs increases. The third finding was that employee’s had adverse emotional reactions after labour force reduction initiatives however the emotions did not manifest to physical reactions such as strikes and employee turnover. The fourth finding was that labour force reduction diminishes production efficiency in the short run (1-3 years) However production efficiency improved in the long run (4-5 years) after labour force reduction. The final finding was that labour force reduction is positively related to financial performance as measured by ROTA.